A Sphingosine-1-Phosphate Lyase Mutation Associated With Congenital Nephrotic Syndrome and Multiple Endocrinopathy - Maharaj, Avinaash; Theodorou, Demetria; Banerjee, Indraneel (Indi); Metherell, Louise A.; Prasad, Rathi; Wallace, Dean (Frontiers in Pediatrics, 2020)
Background: Loss of function mutations in SGPL1 are associated with Sphingosine-1-phosphate lyase insufficiency syndrome, comprising steroid resistant nephrotic syndrome, and primary adrenal insufficiency (PAI) in the majority of cases. SGPL1 encodes sphingosine-1-phosphate lyase (SGPL1) which is a major modulator of sphingolipid signaling. Case Presentation: A Pakistani male infant presented at 5 months of age with failure to thrive, nephrotic syndrome, primary adrenal insufficiency, hypothyroidism, and hypogonadism. Other systemic manifestations included persistent lymphopenia, ichthyosis, and motor developmental delay. Aged 9 months, he progressed rapidly into end stage oligo-anuric renal failure and subsequently died. Sanger sequencing of the entire coding region of SGPL1 revealed the novel association of a rare homozygous mutation (chr10:72619152, c.511A>G, p.N171D; MAF−1.701e-05) with the condition. Protein expression of the p.N171D mutant was markedly reduced compared to SGPL1 wild type when overexpressed in an SGPL1 knockout cell line, and associated with a severe clinical phenotype. Conclusions: The case further highlights the emerging phenotype of patients with loss-of-function SGPL1 mutations. Whilst nephrotic syndrome is a recognized feature of other disorders of sphingolipid metabolism, sphingosine-1-phosphate lyase insufficiency syndrome is unique amongst the sphingolipidoses in presenting with multiple endocrinopathies. Given the multi-systemic and progressive nature of this form of PAI/ nephrotic syndrome, a genetic diagnosis is crucial for optimal management and appropriate screening for comorbidities in these patients.